2014
DOI: 10.1002/jbmr.2381
|View full text |Cite
|
Sign up to set email alerts
|

HDAC5 Controls MEF2C-Driven Sclerostin Expression in Osteocytes

Abstract: Osteocytes secrete paracrine factors that regulate the balance between bone formation and destruction. Among these molecules, sclerostin (encoded by the gene SOST) inhibits osteoblastic bone formation, and is an osteoporosis drug target. The molecular mechanisms underlying SOST expression remain largely unexplored. Here we report that histone deacetylase 5 (HDAC5) negatively regulates sclerostin levels in osteocytes in vitro and in vivo. HDAC5 shRNA increases, whereas HDAC5 overexpression decreases SOST expres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
148
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 142 publications
(153 citation statements)
references
References 63 publications
5
148
0
Order By: Relevance
“…Ocy454 cells show rapid, high level expression of SOST/sclerostin that is responsive to hormonal (PTH), cytokine (PGE 2 ), and mechanical stimuli. Furthermore, G s ␣ knockdown in Ocy454 led to significant increases in SOST expression matching known osteocyte in vivo regulation (35), demonstrating the broad utility of this new osteocytic cell line for studying SOST/sclerostin regulation as we have recently reported (36). Ocy454 also showed an enhanced osteocytic phenotype when cultured on a three-dimensional biomaterial by increasing FGF23 expression upon PTH stimulation, highlighting the importance of optimizing in vitro culture conditions for studying certain aspects of osteocyte biology.…”
mentioning
confidence: 61%
See 2 more Smart Citations
“…Ocy454 cells show rapid, high level expression of SOST/sclerostin that is responsive to hormonal (PTH), cytokine (PGE 2 ), and mechanical stimuli. Furthermore, G s ␣ knockdown in Ocy454 led to significant increases in SOST expression matching known osteocyte in vivo regulation (35), demonstrating the broad utility of this new osteocytic cell line for studying SOST/sclerostin regulation as we have recently reported (36). Ocy454 also showed an enhanced osteocytic phenotype when cultured on a three-dimensional biomaterial by increasing FGF23 expression upon PTH stimulation, highlighting the importance of optimizing in vitro culture conditions for studying certain aspects of osteocyte biology.…”
mentioning
confidence: 61%
“…To confirm these in vivo results in Ocy454 cells, we used shRNA to knock down G s ␣ in Ocy454 as was done previously for HDAC5 (36). The range of sclerostin secretion (normalized to cell number) was determined in each experiment using 10 separate control lentiviruses expressing shRNAs against non-expressed genes (LacZ, luciferase, GFP, and red fluorescent protein).…”
Section: Resultsmentioning
confidence: 87%
See 1 more Smart Citation
“…shRNA to HDAC 4 or 7 in these cells did not increase SOST expression [74]. In subsequent studies, HDAC 5 global knock out mice were shown to have higher numbers of sclerostin secreting osteocytes particularly the periendosteal osteocytes.…”
Section: Hdacs and Inhibitors: Osteocytesmentioning
confidence: 88%
“…These studies are consistent with HDAC 5 suppressing bone formation and selective HDAC 5 inhibitors elevating bone formation, although this has yet to be investigated. In contrast, a recent study revealed that HDAC 5 global knockout mice have reduced numbers of osteoblasts and hence low bone density [74]. This study focused on the fact that HDAC 5 knockout increases SOST expression by osteocytes.…”
Section: Role Of Class II Hdacs In Osteoblast Differentiation and Bonmentioning
confidence: 93%